Drobci ledenodobnega okolja = Fragments of Ice Age Environments Zbornik ob življenjskem jubileju Ivana Turka = Proceedings in honour of Ivan Turk's jubilee - Toškan, Borut (Opera Instituti Archaeologici Sloveniae, 2011)
The monograph Drobci ledenodobnega okolja ("Fragments of Ice Age environments") presents a compilation of seventeen chapters in which experts from different scientific fields discuss specific topics related to the Ice Age in Europe. Ten of them are devoted to the presentation, analysis and interpretation of palaeontological data concerning various large mammal species ranging from mastodon and mammoth to the cave hyena, ibex, cave lion and bears, with the emphasis being placed on the cave bear. Several chapters address the topic of Last Glacial climatic conditions in the Southeastern Alps by studying fossil micromammal and palaeobotanical remains as well as geoarchaeologiocal data. A special article is devoted to a comprehensive review of previous analysis of the bone flute from Divje babe I, but includes also new musicological research findings on the extraordinary technical capabilities of this oldest musical instrument. The concluding chapter presents a study of old manuscripts and printed sources, providing some interesting insights into the discovery of one of the most significant palaeontological sites in Slovenia - the cave of Mokriška jama.The monograph is dedicated to the anniversary of the prominent researcher of the Slovenian Palaeolithic - Ivan Turk. His work, main achievements and selected bibliography are briefly presented in the introductory chapter.